Bronchial Infection and Temporal Evolution of Bronchiectasis in Patients With Chronic Obstructive Pulmonary Disease. (22nd January 2020) - Martínez-García, Miguel Ángel; de la Rosa-Carrillo, David; Soler-Cataluña, Juan Jose; Catalan-Serra, Pablo; Ballester, Marta; Roca Vanaclocha, Yolanda; Agramunt, Marcos; Ballestin, Javier; Garcia-Ortega, Alberto; Oscullo, Grace; Navarro-Soriano, Cristina; Agusti, Alvar
Abstract: Background: Bronchiectasis (BE) impact the clinical course and prognosis of patients with chronic obstructive pulmonary disease (COPD). Yet, the temporal evolution of BE in these patients is unknown. This study seeks to assess the temporal evolution of BE in persons with COPD. Methods: 201 moderate-to-severe patients were recruited between 2004 and 2007 and followed up at least every 6 monts (median of 102 months). To investigate the temporal evolution of BE, in 2015 a second high-resolution computed tomography scan (HRCT) was obtained in survivors and compared with the one obtained at recruitment. Results: 99 (49.3%) died during follow-up. The second HRCT could be obtained in 77 patients and showed that (1) in 27.3% of patients BE never developed, in 36.4% they remained stable, in 16.9% they increased in size and/or extension, and in 19.5% new BE emerged; and that (2) the presence of chronic purulent sputum (hazard ratio [HR], 2.8 [95% confidence interval CI, 1.3–5.8]), number of hospitalizations due to exacerbatons (HR, 1.2 [95% CI, 1.1–1.5]), and number of pathogenic microorganism (PPM) isolations (HR, 1.1 [95% CI, 1.02–1.3]) were independent risk factors for the progression or development of BE. Conclusions: The presence of chronic purulent sputum production, number of PPMs isolated in sputum, and number of hospitalizations due to exacerbations of COPD are independent risk factors of BE progression in patients with COPD. Abstract : The presence of chronic purulent sputum production, number of potentially pathogenic microorganisms isolated in sputum, and number of hospitalizations due to exacerbations of chronic obstructive pulmonary disease (COPD) are independent, preventable, and treatable risk factors of bronchiectasis progression in patients with COPD.